2015
DOI: 10.1016/j.lingua.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Intact grammar in HFA? Evidence from control and binding

Abstract: 4This study contributes original results to the topical issue of the degree to which 5 grammar is intact in high-functioning children with autism (HFA). We examine the 6 comprehension of binding and obligatory control in 26 HFA children, mean age=12;02, 7 compared with two groups of younger typically developing (TD) children: one matched 8 on non-verbal mental age (MA), mean age=9;09, and the other on verbal MA, mean 9 age=8;09. On the binding task, our HFA group showed a good performance on 10 reflexives on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 34 publications
(11 reference statements)
5
24
1
Order By: Relevance
“…Our findings are in accord with the latest findings reported by Janke and Perovic (2015). This recent study showed that 26 British HFA children (non-verbal IQ > 80 as assessed by the Matrices subtest of the KBIT) had intact comprehension of reflexives.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Our findings are in accord with the latest findings reported by Janke and Perovic (2015). This recent study showed that 26 British HFA children (non-verbal IQ > 80 as assessed by the Matrices subtest of the KBIT) had intact comprehension of reflexives.…”
Section: Discussionsupporting
confidence: 94%
“…This is because studies report different results for HFA children and LFA (Boucher, 2009), or for children classified as ALI vs. ALN (Tager-Flusberg, 2006). Nevertheless, the findings from our English-speaking sample of children concur with the findings of English-speaking British children for binding (Janke and Perovic, 2015). These investigations all suggest that children at the high end of the spectrum may not have any kind of syntactic deficiency (e.g., Terzi et al, 2016a,b).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations